Our Odyssey with Functionalized Chiral Phosphines: From Optical Resolution to Asymmetric Synthesis to Catalysis. Issue 1 (18th November 2015) - Chew, Renta Jonathan; Leung, Pak‐Hing
Abstract: Our journey in organophosphorus research over the past 26 years is compiled in this Personal Account. Advances in palladacycle design have engendered a shift in our focus from template‐mediated transformations to catalysis for the direct preparation of chiral phosphines containing a wide variety of functional groups. Novel approaches to access previously inaccessible phosphines and their applications in cancer research are summarized herein. Abstract : Our journey in organophosphorus research over the past 26 years is compiled in this Personal Account. Advances in palladacycle design have engendered a shift in our focus from template‐mediated transformations to catalysis for the direct preparation of chiral phosphines that contain a wide variety of functional groups. Novel approaches to access previously inaccessible phosphines and their applications in cancer research are summarized herein.